2014
DOI: 10.21149/spm.v56i5.7711
|View full text |Cite
|
Sign up to set email alerts
|

Utilización correcta de las técnicas de detección de cáncer de mama en mujeres mexicanas

Abstract: Objetivo. Identificar las características asociadas con la prevalencia de utilización correcta de la autoexploración manual (AE), el examen clínico (EC) y la mamografía (MA) para la detección de cáncer mamario (CaMa). Material y métodos. Se entrevistó a 1 030 mujeres mexicanas, sanas, de entre 20 y 88 años sobre su historia reproductiva y sociodemográfica. Con base en la forma y frecuencia de realización de estas técnicas de detección, se construyó un índice de utilización correcta. Resultados. La prevalencia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
4
0
6
Order By: Relevance
“…One study conducted in Mexico emphasized the importance of nurses to teach BSE and perform CBE, and stated that nurses have a major role in the development of prevention programs, and that BSE and CBE are important strategies to detect and diagnose breast cancer in countries without resources to expand screening by means of MMG (27) .…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted in Mexico emphasized the importance of nurses to teach BSE and perform CBE, and stated that nurses have a major role in the development of prevention programs, and that BSE and CBE are important strategies to detect and diagnose breast cancer in countries without resources to expand screening by means of MMG (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Fátima del Carmen Aguilar-Díaz, D en SP Bucal, (1) fatimaguilar@gmail.com Nora Pérez-Pérez, D en SP Bucal, (2) Miriam Maldonado-Ortega, D en SP Bucal, (3) María del Carmen Villanueva-Vilchis, D en SP Bucal, (1) Javier de la Fuente-Hernández, M en SP Bucal, D en Equid Innov Educ. (1) (…”
Section: Declaración De Conflicto De Intereses Los Autores Declararon No Tener Conflicto De Interesesunclassified
“…Of the 27 studies identified by terms "Risk" and "Breast cancer", 22 were exclusively focused on risk factors, whereas five studies focused on ED (Chart 1). The authors of two out of these five studies defined non-participation on ED and BSE as risk (Chart 1) 28,29 . Their Table 1.…”
Section: The Meaning Of the Term Risk Varied Among Studiesmentioning
confidence: 99%
“…Similarly, one Mexican study focused on socio-economic background of women and risk factors that affect ED (Chart 2) 28 . The authors of this study also analysed the correct application of BSE.…”
Section: Pubmedmentioning
confidence: 99%